Nigeria’s Contribution to Africa’s Regional Integration: Assessment of its recent Performance - Garba, Dimas (African Journal of Politics and Administrative Studies, 2023)
This paper investigates the recent performance of Nigeria towards Africa’s regional integration as a major power in Africa. The main objective of the research is to determine the extent of Nigeria’s commitment to the realization of the African Union’s vision of becoming a fully integrated, prosperous and peaceful Africa; and a dynamic force at the global level. Since her independence in 1960, Nigeria has been widely acknowledged as a leading power in Africa (The Giant of Africa) by several studies because of its preponderant political, economic and militarily power; influence; and benevolent contributions regarding to the liberation and progress of Africa. However, there are hardly substantive assessments of its recent performance towards Africa’s integration. The study adopts the Hegemonic Stability Theory; and descriptive analysis method to analyze data obtained from secondary sources. Analysis of the 2016 and 2019 Regional Integration Index (ARII) reports covering the period from 2010-2019 reveals that Nigeria has performed poorly towards the continent’s integration among its peers, both at the continental and sub-regional levels. The paper concludes that Nigeria’s poor performance would significantly slow the acceleration of Africa’s integration; and the country risks losing its leadership position in Africa to its rivals, especially South Africa. It recommends that the Nigerian government should take deliberate steps in formulating and implementing policies that would improve its performance across the five dimensions of the regional integration; and it should strengthen its commitment to consolidate its leadership position in Africa, and motivate smaller countries to contribute their best.

The Challenges of Regional Integration and Effective Implementation of African Continental Free Trade Area (AfCFTA) Policy in Africa - Garba, Dimas; Wancelous, Avong (African Journal of Politics and Administrative Studies, 2023)
The paper is an investigation of the challenges of regional integration in Africa and their effects on the implementation of the African Continental Free Trade Area (AfCFTA) policy. The major objective of the paper is to proffer solutions to the challenges for the effective actualization of the policy. The assumptions of the neo-liberal theory were used to support the AfCFTA initiative to promote economic growth and development in Africa. The data used to advance the argument were obtained from secondary sources of data collection. The study finds that language barrier, multiple currencies, porosity of borders, foreign interference, political instability and insecurity, poor human development, over-lapping of membership of sub-regional organizations, poor state of infrastructure, and state-centric nature of integration initiatives are some of the core challenges hindering the effective execution of the AfCFTA policy. The study recommends that the African Union (AU) should intensify effort at realizing a single currency policy for Africa; design comprehensive regional security architecture to include high technological surveillance, joint air and ground border patrol among member states of Regional Economic Communities (RECs) to address trans-border crimes and insecurity. There should also be institutionalization of counterpart funding among AU member-states for infrastructural development; and encouragement of private and civil society participation in the integration initiative, among others. In concludes that if the challenges identified are not effectively addressed, it will be very difficult for the AU to successfully realize the objectives of the AfCFTA policy.
Keywords: AfCFTA Policy; Africa; Challenges; Implementation; Regional integration

L'attractivité du droit OHADA - Akonumbo, Atangcho Nji; Monkam, Cyrille; Pironon, Valérie (Institut de Recherche en Droit Privé, 2023)

O processo de constitucionalização dos estados africanos de expressão portuguesa: caminho para um pluralismo jurídico de procedimento - Roda, Arménio Alberto Rodrigues da (Universidade Federal da Bahia, 2023)
Os Estado africanos gozam de uma peculiaridade de possuírem caraterísticas culturalmente heterogêneas, o que acaba tendo um reflexo direto na composição das ordens normativas, as quais compreendem a mesma estrutura híbrida. Com o processo colonial, foram introduzidas na África famílias jurídicas do common Law e civil Law, que foram mantidas no período pós independência, resultando, desse modo, num conflito intersistêmico entre o direito estatal positivista e os direitos africanos – e, em alguns Estados, direito islâmico (Sharia). Diante dessa relação truculenta, a presente pesquisa propõe, em primeiro lugar, o reconhecimento do pluralismo jurídico procedimental e processual, de forma a amenizar esse conflito entre ambas as ordens, no qual o direito positivo arroga-se hegemônico e monista, limitando as manifestações dos direitos consuetudinários. Frisa-se de antemão que essa pesquisa se cinge especialmente aos países africanos de expressão portuguesa, dos quais a Constituição jurídica reconhece formalmente o pluralismo jurídico, todavia na perspectiva meramente substantiva, ou seja, sem métodos claros para efetivação do pluralismo jurídico, seja no âmbito institucional ou na dimensão processual, capaz de integrar os tribunais comunitários e as autoridades tradicionais num ambiente funcionalmente dialógico e plural. Ademais, a pesquisa buscou analisar a forma de funcionamento dos tribunais comunitários que exprimem a manifestação concreta do pluralismo jurídico, tendo sido analisados países como Moçambique, Cabo Verde, Guiné-Bissau e, de forma módica, Angola. Foram descritas as vantagens dos tribunais comunitários para o acesso à justiça e as suas limitações inerentes a certos direitos e certas garantias fundamentais que correm risco de serem violados, como o devido processo, negação da igualdade formal das mulheres e direitos das crianças. Para tal, foi proposta a possibilidade de fiscalização desses tribunais e participação de juízes profissionais em casos de grande magnitude. Sem embargos, cabe mencionar que foi trazida à discussão o paradigma pós positivista como um mecanismo de superação do positivismo puro, admitindo uma correção do direito pela moral, no sentido proposto por Robert Alexy (2009) e com nuances argumentativas compatíveis com a realidade africana, apresentado no terceiro capítulo em que se discuti a questão da crise do positivismo no continente africano. Frisa-se também que foi agregado a esse trabalho uma argumentação voltada à possibilidade de constitucionalização de Ubuntu como um princípio constitucional, parte dos direitos africanos, constituindo um mecanismo de incorporação e codificação plural dos valores africanos nos leques das normas estatais. Além do que já foi dito, foi analisada a questão ligada à efetividade dos direitos fundamentais, sobretudo os direitos das mulheres, tendo enaltecido a viabilidade de um constitucionalismo feminista, que pugna pela justiça de gênero na África, especialmente nas questões concernentes aos direitos reprodutivos e ao acesso às mesmas oportunidades. Por fim, descreveu-se o modelo das cortes constitucionais e o seu papel para a garantia e promoção dos direitos fundamentais. African states have the peculiarity of having culturally heterogeneous characteristics, which ends up having a direct impact on the composition of their legais systems, which comprise the same hybrid structure. With the colonial process, common law and civil law legal families were introduced in Africa, which were maintained in the post-independence period, thus resulting in an intersystemic conflict between positivist state law and African rights - and, in some states, Islamic law (Sharia). Faced with this truculent relationship, this research proposes, firstly, recognising procedural and procedural legal pluralism, in order to ease this conflict between the two orders, in which positive law claims to be hegemonic and monistic, limiting the manifestations of customary rights. It should be noted beforehand that this research is particularly focused on Portuguese-speaking African countries, whose legal constitution formally recognises legal pluralism, but from a purely substantive perspective, i.e. without clear methods for making legal pluralism effective, either in the institutional sphere or in the procedural dimension, capable of integrating community courts and traditional authorities in a functionally dialogical and plural environment. In addition, the research sought to analyse the way in which community courts that express the concrete manifestation of legal pluralism operate, having analysed countries such as Mozambique, Cape Verde, Guinea-Bissau and, in a modest way, Angola. The advantages of community courts for access to justice were described, as well as their inherent limitations with regard to certain fundamental rights and guarantees that are at risk of being violated, such as due process, denial of formal equality for women and children's rights. To this end, the possibility of supervising these courts and involving professional judges in cases of great magnitude was proposed. It is worth mentioning that the post-positivist paradigm was brought into the discussion as a mechanism for overcoming pure positivism, admitting a correction of the law by morality, in the sense proposed by Robert Alexy (2009) and with argumentative nuances compatible with the African reality, presented in the third chapter in which the issue of the crisis of positivism on the African continent is discussed. It should also be noted that this work includes an argument for the possibility of constitutionalising Ubuntu as a constitutional principle, part of African rights, constituting a mechanism for the incorporation and plural codification of African values into state norms. In addition to what has already been said, the issue of the effectiveness of fundamental rights, especially women's rights, was analysed, highlighting the viability of a feminist constitutionalism that strives for gender justice in Africa, especially on issues concerning reproductive rights and access to the same opportunities. Finally, the model of constitutional courts and their role in guaranteeing and promoting fundamental rights were described.
Keywords: Community courts; Constitucionalismo - África; Direitos humanos; Human rights; Justiça tradicional; O processo histórico do constitucionalismo africano; Pluralismo jurídico; Pluralismo jurídico procedimental; Procedural legal pluralism; Traditional justice; Tribunais comunitários

The Position of General Principles of Law in the Interpretation of Treaties - Hajjar, Mahmoud; Zamani, Seyed Ghasem (Public Law Researsh, 2023)
The interpretation of treaties is particularly important in the field of treaty law, as in most cases it is not possible to apply treaties without their interpretation. In addition to the text and context of the treaty, the relevant rules of international law, including the general principles of law, can play an important role in the interpretation of treaties. A treaty is a creation of the international legal system, and its interpretation and implementation should be carried out within the context of the legal system that governs it. The main question to which this research intends to answer is: What is the position of general principles of law in the interpretation of treaties? It seems that the use of general principles of law in the interpretation of treaties can reduce the potential fragmentation of international law and promote its coherence. In this research, by using library sources, international documents and international judicial decisions and arbitration awards and using a descriptive-analytical method, the position of general principles of law in the interpretation of treaties will be examined.
Keywords: Article 31 (3) (C) of the Convention of the Law of Treaties; General Principles of Law; International Jurisprudence; Interpretation of Treaties; Systemic Integration

La rénovation des cadres juridiques de gouvernance foncière dans les pays en développement : étude de cas croisée du Niger, d'Haïti et de l'Afrique du Sud - Pennec, Jérôme (Université de Bretagne Occidentale, 2023)
Le travail de recherche examine les processus d’élaboration et de mise en œuvre de nouveaux cadres juridiques de gouvernance foncière dans les pays en développement. Par le biais de trois pays d’étude de contextes juridiques, historiques et culturels très différents, à savoir le Niger, Haïti et l’Afrique du Sud, l’analyse met en évidence que les réformes foncières dans les pays en développement sont confrontées à certaines problématiques juridiques et difficultés de mise en œuvre communes. Elle démontre les limites des modèles classiques et techniques de gouvernance foncière, ainsi que les failles du cadre international et l’influence de l’aide internationale en la matière. Elle souligne également l’importance de prendre en considération les multiples pratiques sociales en lien avec l’accès et l’usage des terres, qui dépassent largement la seule notion classique de propriété. Sur la base de ce constat, la thèse établit que la prise en compte des pluralités juridiques est un élément clé pour envisager la rénovation des cadres juridiques du foncier, mais que cette étape à elle seule n’est pas suffisante pour créer un système efficient de gouvernance foncière. Il apparaît ainsi nécessaire de penser l’organisation de ces pluralités au sein d’un véritable système pluraliste ordonné. L’analyse évoque les éléments concrets de mise en application de ce concept à des échelles nationales. This paper examines the design and implementation processes of new legal frameworks for land tenure in developing countries. In the light of three case studies with different legal, historical and cultural contexts – namely Niger, Haïti and South Africa – the study shows that they all face the same legal and implementation challenges while carrying out such reforms. The study highlights the limitations of classical and technical land tenure governance models as well as the weaknesses of the international framework and the influence of international assistance on this subject. Moreover, it demonstrates the need to consider the different social practices of land access and use, which go beyond the sole notion of land property. Building on this assessment, the study shows that the examination of legal pluralim is fundamental to consider the reform of land tenure’s legal frameworks, even though this step is not sufficient to create an efficient system for land tenure governance. It seems thus necessary to think the organization of these pluralities within a truly pluralist and ordered system. The study puts forward concrete, hands-on elements for implementing this concept at national levels.
Keywords: Afrique du Sud; Developing countries; Gouvernance foncière; Haïti; Land reform; Legal pluralism; Niger; Pays en développement; Pluralisme juridique; Réforme agraire; South Africa

La répartition des compétences entre la CEMAC et ses États membres - Allamaye Golbey, Levi (Revue Africaine et Malgache de Recherches Scientifiques : Sciences juridiques et politiques, 2023)
The Uniform Act relating to the law of commercial companies and of economic interest groups contains numerous references to the concept of act, without the legislator being able to specify its meaning. This legislative silence is the pretext for the doctrine to give this notion several perceptions, without any of them being able to give its full dimension in isolation. Beyond this polysemy, it is revealed through the notion of act, a plurality of purposes that the legislator intends to assign to it in company law, by making it an instrument at the service of the partners and third parties. In relations between partners, the concept of act ensures an objective of regulating relations when the legislator requires, both in the phases of incorporation and of the functioning of the company, that the acts be coated with the seal of authenticity and that they are carried out according to the required standards. The OHADA legislator also invokes the concept of acts when it comes to ensuring the third party who comes to deal with the company or its members the protection of his interests. From this point of view, the prerequisite required for such an act to achieve this objective is compliance with certain conditions. Otherwise, when we analyze the regime for the resumption of acts performed during the period constituting the commercial company and certain situations, we are reinforced in this idea of protection assigned to the concept of act.

Genre et gouvernance dans l’émergence de la CEEAC - Alima Tolo, Marie-Micheline (Revue Africaine des Réflexions Juridiques et Politiques, 2023)
La présente contribution trouve son fondement sur l’hypothèse selon laquelle pour atteindre l’émergence escomptée en 2025 et rendre ses économies plus résilientes et plus attractives, les États de la Communauté Économique des États de l’Afrique Centrale (CEEAC) doivent prendre en compte le genre. Il ne s’agit pas de conjuguer avec le tout-venant pour une participation numérique, mais de composer avec des citoyens outillés, conscients de leur rôle et des enjeux qui nécessitent leur action. Cette réflexion explore ainsi de manière conjointe les pans de la gouvernance et de l’économie, qui constituent les piliers du développement. Elle met au cœur de son mouvement la formation de toutes les composantes de la population, l’accent étant davantage mis sur les femmes, véritable capital qui tend à être mal exploité, car confinées dans un espace où elles ne laissent pas éclore l’étendue de leurs talents. La réalité est que, la marginalisation et l’ostracisme constituent des goulots d’étranglement dans une dynamique évolutionniste et ne sauraient de ce fait servir les intérêts des Etats engagés. Ces réalités réductrices de l’efficacité tous azimuts sont non conformes à l’esprit d’émergence dans le sens qu’ils musellent considérablement les ressources capables d’impulser une réelle dynamique développementaliste en les rendant inopérantes. D’où l’urgence d’une approche inclusive.
Keywords: Emergence; Entrepreneuriat; Entrepreneurship; Gender; Genre; Gouvernance; Governance; Inclusion

Coopération et intégration sous régionale : l’Afrique Centrale au tribunal de la raison - Boulingui Moussavou, Alain (Revue Africaine des Réflexions Juridiques et Politiques, 2023)
Cette analyse discute les questions de coopérations et d’intégrations que connaît l’Afrique centrale à l’aune du transhumanisme. La coopération et l’intégration visent la compréhension interétatique en vue de renforcer la solidarité et la fraternité. Pour faciliter cette coopération et les intégrations, les responsables politiques de l’Afrique centrale et des grands lacs qui partagent une destinée commune vont, pour leur progrès social, économique et politique, se munir d’organisations sensées faciliter l’intégration. Cependant, force est de constater que la mise en pratique des mécanismes d’intégration contraste avec la dynamique de coopération politique.
Keywords: Afrique centrale; Coopération; Développement; Institutions; Intégration

La problématique de la question migratoire dans les espaces CEDEAO et CEMAC - Cissé, Salif (Revue Africaine des Réflexions Juridiques et Politiques, 2023)
Cet article abordera les causes profondes des migrations forcées dans les espaces CEDEAO et CEMAC. Les conflits, l’insécurité, la dégradation de l’environnement et la pauvreté constituent des causes profondes des migrations de masse et des déplacements forcés en dans les espaces CEDEAO et CEMAC. L’inégalité mondiale, le manque d’emploi et de travail décent, la pauvreté, les conflits, les inégalités entre les sexes et la discrimination, le terrorisme et les pressions climatiques continuent de pousser les gens à rechercher une vie meilleure à l’étranger. Les flux mixtes composés de différents types de migrants et de demandeurs d’asile qui utilisent les mêmes voies et moyens de migration, sont revus à la hausse.
Keywords: CAEMC; CEDEAO; CEMAC; ECOWAS; Inégalité mondiale; Migrant; Migration

Les Communautés économiques régionales, améliorent-elles le commerce intrarégional dans le cadre de la ZLECAf ? - El Bekri, Hafsa (Revue Interventions économiques, 2023)
Cet article examine l’impact des facteurs de proximité sur l’intensité commerciale intra africaine. Dans le cadre des modèles reposant sur une approche ex post, notre contribution concerne l’usage d’un modèle de gravité avec la prise en compte des distances géographiques et économiques. Nos résultats montrent que les niveaux d’intégration commerciale contrastés au sein des CER risquent d’accentuer l’asymétrie d’intégration continentale, ils révèlent que la distance économique impacte positivement et significativement l’intensité des échanges et suggèrent le renforcement de l’intégration via les chaines de valeur régionales. This article examines the impact of proximity factors on intra-African trade intensity. Our contribution consists of the use of a gravity model with the consideration of geographical and economic distances. Our results show that the contrasting levels of trade integration within the RECs are likely to accentuate the asymmetry of continental integration, they reveal that economic distance has a positive and significant impact on the intensity of trade and suggest the strengthening of integration through regional value chains.
Keywords: AfCFTA; Afrique; Bilateral intensities; Commerce intra-régional; Communautés économiques régionales; Facteurs de proximité; Intra-African trade; Modèle de gravité; Proximity factors; Regional integration

Pour la constitutionnalisation des ordres juridiques communautaires en Afrique de l’ouest francophone : le cas de l’ordre juridique UEMOA - Essenouwa, Kodjo Tognissé (Revue Africaine des Réflexions Juridiques et Politiques, 2023)
La constitutionnalisation des ordres juridiques communautaires s’affiche comme une alternative crédible aux conflits des normes inter-systémiques dans l’espace juridique ouest-africain francophone. L’hypothèse a l’avantage de faire intégrer les normes communautaires au bloc de constitutionnalité et, ce faisant, constitue l’opportunité de faire du juge constitutionnel non seulement un garant potentiel de l’application du droit communautaire mais aussi un interlocuteur probable des Cours de justice communautaire. Heureusement, il existe dans le constitutionnalisme d’Afrique de l’Ouest francophone des moyens juridiques de sa concrétisation.
Keywords: Community legal order; Constitutionalization; Constitutionnalisation; Norm; Norme; Ordre juridique communautaire

L’Organisation pour l’harmonisation en Afrique du droit des affaires en quête de règles uniformes de droit international privé : état des lieux et perspectives - Marque, Étienne (Les Cahiers de droit, 2023)
L’Organisation pour l’harmonisation en Afrique du droit des affaires (OHADA) s’est depuis peu engagée sur la voie de l’uniformisation des règles de droit international privé de ses États membres. Une telle entreprise est sans précédent pour cette organisation. Pour la première fois en trois décennies d’existence, le domaine de l’uniformisation ne sera en effet pas celui de l’arbitrage ou du droit substantiel des affaires, mais celui du traitement des relations d’affaires ayant des éléments de rattachement avec plusieurs ordres juridiques. Ce projet d’acte uniforme est bienvenu à plus d’un titre. Il comblerait d’abord un déficit patent de règles de droit international privé dans un espace qui intègre pourtant 17 États, et qui est donc propice aux relations d’affaires internationales. En oeuvrant désormais à l’articulation des lois et des juridictions nationales de ses États membres, le droit OHADA prendrait de surcroît le contre-pied de son approche traditionnelle qui consistait jusqu’alors à les neutraliser. Plus qu’un nouvel acte uniforme, ce projet constitue donc un important changement d’orientation pour l’OHADA.

Recueil de textes communautaires sur la libre circulation et le droit d'établissement - Union Economique et Monétaire Ouest Africaine (UEMOA, 2023)